Ventricular fibrillation due to lithium withdrawal–an interaction with chlorpromazine?. Issue 770 (December 1989) - Stevenson, R. N.; Blanshard, C.; Patterson, D. L.
Abstract : We report a case of primary ventricular fibrillation following withdrawal of lithium in a patient concurrently taking chlorpromazine. A potentially important drug interaction is discussed.